2003
DOI: 10.1038/sj.jhh.1001579
|View full text |Cite
|
Sign up to set email alerts
|

Nitrendipine and amlodipine mimic the acute effects of enalapril on renal haemodynamics and reduce glomerular hyperfiltration in patients with chronic kidney disease

Abstract: Antihypertensive drugs may have an important effect on glomerular haemodynamics. In chronic nephropathy patients, we compared the effect on glomerular haemodynamics of two second-generation dihydropyridinic agents, nitrendipine and amlodipine, with a first generation dihydropyridinic agent and an ACE-inhibitor, enalapril. In all, 32 patients (pts), divided into four groups, received the different drugs: ENA (enalapril, eight pts), NIF (nifedipine, eight pts), NIT (nitrendipine, eight pts) AML (amlodipine, eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although some studies have reported the effect of L/T-, L/N-, or L/N/T-type CCBs on estimated GFR (eGFR), their results vary according to concomitant drugs, treatment duration, and medical history of the patients [ 6 , 7 , 10 ]. In addition, some CCBs are known to cause an increase in GFR, hyperfiltration, and edema in the acute phase of initiation of treatment in patients with CKD [ 11 13 ]. Agodoa et al reported that eGFR increased during the first 3 months of treatment with amlodipine, an L-type CCB, but decreased after 36 months in patients without proteinuria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported the effect of L/T-, L/N-, or L/N/T-type CCBs on estimated GFR (eGFR), their results vary according to concomitant drugs, treatment duration, and medical history of the patients [ 6 , 7 , 10 ]. In addition, some CCBs are known to cause an increase in GFR, hyperfiltration, and edema in the acute phase of initiation of treatment in patients with CKD [ 11 13 ]. Agodoa et al reported that eGFR increased during the first 3 months of treatment with amlodipine, an L-type CCB, but decreased after 36 months in patients without proteinuria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is more likely that amlodipine raised GFR early in the disease and returned to normal levels after 12 weeks due to glomerular injury. Variable effects of CCBs on GFR have been reported in other models and humans [14, 17, 35]. In patients with chronic, nondiabetic renal disease and in patients with mild to moderate essential hypertension, amlodipine increased GFR and glomerular capillary pressure [35].…”
Section: Discussionmentioning
confidence: 99%
“…Variable effects of CCBs on GFR have been reported in other models and humans [14, 17, 35]. In patients with chronic, nondiabetic renal disease and in patients with mild to moderate essential hypertension, amlodipine increased GFR and glomerular capillary pressure [35]. In type 2 diabetic patients with hypertension and nephropathy a significant decrease in estimated GFR was observed after treatment with amlodipine [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, amlodipine seems to have renoprotective effects in CKD patients, especially when paired with ARBs , probably due to a reduction in renal artery smooth muscle contraction leading to a higher renal flow, even while systemic blood pressure is reduced . Indeed, even a single dose of amlodipine can lead to a demonstrable increase in eGFR in CKD patients .…”
Section: Relationship Between Heart Failure and Renal Failurementioning
confidence: 99%